2014
DOI: 10.1111/acel.12273
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restriction involves NAD+‐dependent mechanisms and a shift toward oxidative metabolism

Abstract: Interventions that slow aging and prevent chronic disease may come from an understanding of how dietary restriction (DR) increases lifespan. Mechanisms proposed to mediate DR longevity include reduced mTOR signaling, activation of the NAD+-dependent deacylases known as sirtuins, and increases in NAD+ that derive from higher levels of respiration. Here, we explored these hypotheses in Caenorhabditis elegans using a new liquid feeding protocol. DR lifespan extension depended upon a group of regulators that are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 47 publications
4
68
0
2
Order By: Relevance
“…7C). This residual effect could be due to SKN-1b and SKN-1-independent mechanisms (Bishop and Guarente, 2007;Moroz et al, 2014). 3.7.…”
Section: Genetic Interactions Between Wdr-23 and Other Longevity Pathmentioning
confidence: 99%
See 4 more Smart Citations
“…7C). This residual effect could be due to SKN-1b and SKN-1-independent mechanisms (Bishop and Guarente, 2007;Moroz et al, 2014). 3.7.…”
Section: Genetic Interactions Between Wdr-23 and Other Longevity Pathmentioning
confidence: 99%
“…(A-F) P values of <0.0167 were taken to indicate statistical significance. longevity (Iwasa et al, 2010;Jung and Kwak, 2010;Moroz et al, 2014). Over the last three decades, hundreds of genes and diverse pathways have been identified that influence lifespan, but understanding how these genes and pathways influence specific aging processes is far more limited.…”
Section: The Skn-1/wdr-23 Pathway Delays Degenerative Tissue Changes mentioning
confidence: 99%
See 3 more Smart Citations